Strategi Guru Pendidikan Agama Islam dalam Pembinaan Akhlakul Karimah Peserta Didik di SMP PGII 2 Bandung - Intan Surya Hadiatulloh; Surana, Dedih (UNISBA Press, 2024)
Abstract. The human moral crisis in the post-covid 19 era is increasingly concerning, morals are only limited to entertainment and comedians. Such as showing off the glittering world of the night on social media, not old enough, engaging in alcoholic beverages and much more. The purpose of this study is to find out the program of Islamic education teachers in fostering akhlakul karimah students,to find out the approach and methods of Islamic education teachers in fostering akhlakul karimah and to find out the supporting and inhibiting factors in the development of akhlakul karimah. This study used qualitative research with a descriptive approach. The data collection used is observation, interviews and documentation. The data that has been obtained is analyzed by reducing the data, presenting the data and drawing conclusions. The research results show that (1) the PAI teacher is the morning habituation program, afternoon habituation program, afternoon habituation program, 5S program, routine recitation program, and Islamic holiday commemoration program. (2) PAI teachers' approaches and methods is namely example, habituation, competence, advice, punishment, exercise, correction, advice methods, lectures and stories. (3) Inhibiting and supporting factors is namely supporting factors, foundation and school policies, GDS (Student Discipline Movement) team and religious team, facilities and infrastructure, school community, and students' pocketbooks. Inhibiting factors are students, family environment, community environment, time constraints and poor coordination with SMA PGII 2 Bandung. Abstrak. Krisis moral manusia pada zaman sesudah covid 19 semakin memprihatinkan, moral hanya sebatas hiburan dan komedian semata. Seperti memamerkan dunia gemerlap malam di media sosial belum cukup umur, terlibat minuman beralkohol dan masih banyak lagi. Tujuan penelitian ini yaitu (1) untuk mengetahui program guru pendidikan Agama Islam dalam pembinaan akhlakul karimah peserta didik, (2) untuk mengetahui pendekatan dan metode guru pendidikan Agama Islam dalam pembinaan akhlakul karimah, (3) untuk mengetahui faktor pendukung dan penghambat dalam pembinaan akhlakul karimah. Penelitian ini menggunakan penelitian kualitatif dengan pendekatan deskriptif. Pengumpulan data yang digunakan adalah observasi, wawancara dan dokumentasi. Data yang telah diperoleh dianalisis dengan mereduksi data, memaparkan data dan menarik kesimpulan. Hasil penelitian menunjukan bahwa (1) program guru PAI yaitu program pembiasaan pagi, program pembiasaan siang, program pembiasaan sore, program 5S, program pengajian rutin, dan program peringatan hari besar Islam. (2) Pendekatan dan metode guru PAI yaitu teladan, pembiasaan, kompetensi, anjuran, latihan, hukuman,koreksi, metode nasihat, ceramah dan kisah-kisah. (3) Faktor penghambat dan pendukung yaitu Faktor pendukung, kebijakan yayasan dan sekolah, tim GDS (Gerakan Disiplin Siswa) Dan tim keagamaan, sarana dan prasarana, sivitas sekolah, dan buku saku peserta didik. Faktor penghambat yaitu peserta didik, lingkungan keluarga, lingkungan masyarakat, keterbatasan waktu dan koordinasi kurang baik dengan SMA PGII 2 Bandung.